Fabricação e caracterização elétrica de dispositivos orgânicos emissores de luz derivados de poli-p(fenilene vinilene) (PPV) - Amorim, Cleber Alexandre de (Universidade Federal de São Carlos, 2010)
Molecularly doped polymers have been widely studied in recent years due to their electronic and optical properties, and application in the manufacture of opto-electronic devices, light emitting diodes (LED) and others. These materials are very promising since they can be used in the manufacture of common and flexible displays and reduced thickness screens, and they also offer low power consumption and high image quality. A series of polymers has been studied and despite the importance of these materials and all the knowledge acquired in the past years, the transport mechanism is still partially unknown. The mobility of charge carrier and the exact nature of the states are little studied due to experimental problems found in a conventional measurement of transit time and especially in low thickness samples. Because of that, this present work aims the manufacturing and electrical and optical characterization of polymer devices, and implements a new and powerful technique to determine structures mobility of a few hundred nanometers of thickness. This technique is based on Charge Extraction in a Linearly Increasing Voltage, CELIV. Beside determining the mobility, we have studied result validity by comparing them to more conventional techniques such as TOF - time of flight, DI-SCLC Dark Injection current limited by space charge and characterization J vs. V, where J is the current density and V the voltage applied, reaching thickness when techniques such as TOF and DI-SCLC are no longer valid. Another focus of this work is to use mobility to study structures degradation and examine how the mobility of samples stored behaves in different ways, vacuum and air, over time and how this interferes with the process of carrier injection.
Keywords: Propriedades eletrônicas; Polímeros; Transporte eletrônico; CIENCIAS EXATAS E DA TERRA::FISICA